Fundamentals of database systems - Elmasri, Ramez (Addison-Wesley, 2011)
Clear explanations of theory and design, broad coverage of models and real systems, and an up-to-date introduction to modern database technologies result in a leading introduction to database systems. Intended for computer science majors, Fundamentals of Database Systems, 6/e emphasizes math models, design issues, relational algebra, and relational calculus.